The real and expected privileges of the Security Service collaborators recruited from academic milieu in the 1980s - Franaszek, Piotr (Studia Historiae Oeconomicae, 2015)
Despite the elaborated techniques of electronic surveillance, personal sources of information still remain the best possible method of infiltrating a criminal milieu. Such methods gain special importance in totalitarian states. Collaborating with the Security Service almost always had some notable benefits. For some of the TWs, collaborating was an additional, sometimes quite substantial, source of income. One of repeating motives for collaboration was a will to improve one’s professional position or to easily obtain a permission to go abroad. There were also persons, who were impressed with having contacts with the Security Service functionaries. Almost all collaborators were using different forms of help from the part of the Security Service. Most of them would obtain real financial and material profits. The spectrum of favours offered to those helping the repressive state apparatus was very extensive.